PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN KEDISIPLINAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BTN CABANG SYARIAH PEKANBARU - JELI NATA LIYAS (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2018)
The purpose of this study was to determine the influence of Leadership Style, Motivation and Discipline on work performance on employee performance in PT. Bank Tabungan Negara (Persero) Tbk Kantor Cabang Syariah Pekanbaru. Data analysis used is multiple linear regression analysis. The sample of this study are 35 respondents who are permanent employees in PT. Bank Tabungan Negara (Persero) Tbk Kantor Cabang Syariah Pekanbaru. The variables used are Leadership Style, Motivation and Discipline of work achievement. The results showed that the three variables tested simultaneously have a significant effect on employee performance in PT. Bank Tabungan Negara (Persero) Tbk Kantor Cabang Syariah Pekanbaru. Partially Leadership Style significantly influence, while Motivation and Discipline of work achievement does not significantly influence. Leadership, Motivation and Discipline Variables on work performance have an effect of 8.36% on employee performance while the remaining 16,4% is influenced by other variables not included in the research.